Activation of Dynamin-Related Protein 1 and Induction of Mitochondrial Apoptosis by Exosome-Rifampicin Nanoparticles Exerts Anti-Osteosarcoma Effect - Chen W; Lin W; Yu N; Zhang L; Wu Z; Chen Y; Li Z; Gong F; Li N; Chen X; He X; Wu Y; et al. (International Journal of Nanomedicine, 2022)
Wenkai Chen,1,2,* Wenping Lin,3,* Naichun Yu,1,2,* Linlin Zhang,1,2,* Zuoxing Wu,2 Yongjie Chen,1,2 Zongguang Li,1,2 Fengqing Gong,1,2 Na Li,2 Xiaohui Chen,4 Xu He,3 Yue Wu,5 Xiangchen Zeng,1,2 Yuting Yueh,1,2 Ren Xu,2,4,6,* Guangrong Ji1,2,* 1Department of Orthopedic Surgery, Xiang’an Hospital of Xiamen University, School of Medicine, Xiamen University, Xiamen, People’s Republic of China; 2Fujian Provincial Key Laboratory of Organ and Tissue Regeneration, Xiamen Key Laboratory of Regeneration Medicine, Organ Transplantation Institute of Xiamen University, School of Medicine, Xiamen University, Xiamen, People’s Republic of China; 3Department of Spine Surgery, Shenzhen Pingle Orthopedic Hospital, Affiliated Hospital of Guangzhou University of Traditional Chinese Medicine, Shenzhen, People’s Republic of China; 4Department of Orthopedic Surgery, The First Affiliated Hospital of Xiamen University, Xiamen, People’s Republic of China; 5Department of Pathology, Zhongshan Hospital, Xiamen University, Xiamen, People’s Republic of China; 6Collaborative Innovation Centre of Regenerative Medicine and Medical BioResource Development and Application Co-Constructed by the Province and Ministry, Guangxi Medical University, Nanning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guangrong Ji; Ren Xu, Department of Orthopedic Surgery, Xiang’an Hospital of Xiamen University, No. 2000, Xiang’an East Road, Xiang’an District, Xiamen, 361000, People’s Republic of China, Tel +86-15710667257, Fax +86592-2889000, Email jiguangrong@xmu.edu.cn; xuren526@xmu.edu.cnPurpose: To investigate induction of cell death in Osteosarcoma (OS) using the anti-tuberculosis drug, rifampicin, loaded into exosomes.Patients and Methods: BMSC-exosomes were isolated by ultracentrifugation and loaded ultrasonically with rifampicin. Nanoparticle exosome-rifampicin (EXO-RIF) was added to the OS cell-lines, 143B and MG63, in vitro, to observe the growth inhibitory effect. In vivo experiments were conducted by injecting fluorescently labeled EXO-RIF through the tail vein of 143B cell xenograft nude mice and tracking distribution. Therapeutic and toxic side-effects were analyzed systemically.Results: Sonication resulted in encapsulation of rifampicin into exosomes. Exosome treatment accelerated the entry of rifampicin into OS cells and enhanced the actions of rifampicin in inhibiting OS proliferation, migration and invasion. Cell cycle arrest at the G2/M phase was observed. Dynamin-related protein 1 (Drp1) was activated by EXO-RIF and caused mitochondrial lysis and apoptosis. Exosome treatment targeted rifampicin to the site of OS, causing OS apoptosis and improving mouse survival in vivo.Conclusion: The potent Drp1 agonist, rifampicin, induced OS apoptosis and exosome loading, improving OS targeting and mouse survival rates. EXO-RIF is a promising strategy for the treatment of diverse malignancies.Graphical Abstract: Keywords: bone tumor, drug delivery, exosomes, mesenchymal stem cells, survival